P925 An analysis of the impact of etiology vs. impact of hemodynamic variables on the right ventricular free wall deformation in patients with pulmonary hypertension. (17th January 2020) - Ojrzynska, N; Kowalik, E; Kowalski, M; Klisiewicz, A; Demkow, M; Witkowski, A; Grzybowski, J
Abstract: Purpose: Pulmonary hypertension (PH) is a deadly disease leading to right ventricular (RV) failure. The aim of this study was to establish whether aetiology of PH has a greater impact on RV longitudinal deformation than cardiac catherization parameters. Methods: We retrospectively analyzed echocardiographic studies and cardiac catherization parameters of 25 patients with pulmonary hypertension : 13 pts with precapillary PH associated with atrial/ventricular septum defect and 12 pts with postcapillary PH due to dilated cardiomyopathy. We measured regional strain and regional systolic and diastolic strain rates (SR) in right ventricular free wall in basal, mid and apical segments. Results: Aside from TAPSE, echocardiographic parameters indicate no difference. Even though mean pulmonary arterial pressure and pulmonary vascular residence significantly higher in patients with precapillary PH, strain was significantly decreased in patients with postcapillary PH. Statistically significant differences were observed between pre- and postcapillary PH patients" strain in apical and mid myocardial segments. Early diastolic strain rate (SR) in apical RV segment in precapillary PH patients was significantly higher than in patients with postcapillary PH. In other myocardial segments there were no differences between systolic, early diastolic and late diastolic SR. Conclusion: Our study suggests that RV free wall strain in patients with PH moderately correlate with aetiology of PH. We did not find correlation between higher RA pressure or PVR and worsening of RV function in PH of different aetiologies.